Renal Dysfunction Induced by Kidney-Specific Gene Deletion of Hsd11b2 as a Primary Cause of Salt-Dependent Hypertension. Issue 1 (July 2017) - Ueda, Kohei; Nishimoto, Mitsuhiro; Hirohama, Daigoro; Ayuzawa, Nobuhiro; Kawarazaki, Wakako; Watanabe, Atsushi; Shimosawa, Tatsuo; Loffing, Johannes; Zhang, Ming-Zhi; Marumo, Takeshi; Fujita, Toshiro
Abstract : Genome-wide analysis of renal sodium-transporting system has identified specific variations of Mendelian hypertensive disorders, including HSD11B2 gene variants in apparent mineralocorticoid excess. However, these genetic variations in extrarenal tissue can be involved in developing hypertension, as demonstrated in former studies using global and brain-specific Hsd11b2 knockout rodents. To re-examine the importance of renal dysfunction on developing hypertension, we generated kidney-specific Hsd11b2 knockout mice. The knockout mice exhibited systemic hypertension, which was abolished by reducing salt intake, suggesting its salt-dependency. In addition, we detected an increase in renal membrane expressions of cleaved epithelial sodium channel-α and T53-phosphorylated Na + -Cl − cotransporter in the knockout mice. Acute intraperitoneal administration of amiloride-induced natriuresis and increased urinary sodium/potassium ratio more in the knockout mice compared with those in the wild-type control mice. Chronic administration of amiloride and high-KCl diet significantly decreased mean blood pressure in the knockout mice, which was accompanied with the correction of hypokalemia and the resultant decrease in Na + -Cl − cotransporter phosphorylation. Accordingly, a Na + -Cl − cotransporter blocker hydrochlorothiazide significantly decreased mean blood pressure in the knockout mice. Chronic administration of mineralocorticoid receptor antagonist spironolactone significantly decreased mean blood pressure of the knockout mice along with downregulation of cleaved epithelial sodium channel-α and phosphorylated Na + -Cl − cotransporter expression in the knockout kidney. Our data suggest that kidney-specific deficiency of 11β-HSD2 leads to salt-dependent hypertension, which is attributed to mineralocorticoid receptor–epithelial sodium channel–Na + -Cl − cotransporter activation in the kidney, and provides evidence that renal dysfunction is essential for developing the phenotype of apparent mineralocorticoid excess. Abstract : Supplemental Digital Content is available in the text.